OPTIMASI KUALITAS KEMBANG GULA LUNAK DARI BUAH NANAS (Ananas comosus L) KARENA PERBEDAAN KONSENTRASI SIRUP GLUKOSA DAN PUTIH TELUR - Setyono, Rahmat Edy; Sihmawati, Rini Rahayu; Rosida, Dwi Agustiyah (Heuristic, 2015)
The aim of this research was to know the effect of glucose syrup and albumen to quality of pineapple softcandy in physical, chemical and organoleptic and to know the right glucose syrup and albumen concentration of the making pineapple softcandy.The research used Completely Randomized Block Design, with consist of 3 level with 3 times repeat , the glucose syrup ( G) ( 35%,50%, 65%) and albumen ( A) ( 2%, 4%, 6%).Chemical properties of the test include water content, reducing sugar and physic properties such as texture and sensory testing include flavor and color. Obtained data were tested using ANOVA followed by BNT if it showed the real difference in treatment and used DMRT if there were interaction between two factor. The results of this research showed that the addition of glucose syrup and egg albumen real effect on reducing sugar levels and no real effect on the moisture content and texture of pineapple softcandy . The average sugar content is highest reduction in treatment G3A3 (35 .107%) and the lowest in treatment G1A1 (34 163%). Differences in execution time trial showed no significant differences in effect on all parameters tested. Organoleptic test results showed the majority of panelists do not like to color soft confectionery pineapple. As for the taste of the most preferred in the treatment G3A3.Kata kunci : kembang gula lunak, sirup glukosa, putih telur, buah nanas